مخـاطر البلد واثرها على حجم الاستثمارات الوافدة دراسة قياسية :الجزائر خلال الفترة ( 1990-2014) - سيسانى, د.ميدون (Recherches économiques et managériales, 2017)
تتسابق معظم دول العالم المتقدم و النامي على جذب الاستثمارات الاجنبية المباشرة  نتيجة لدوره في حل المشكلات التنموية.و تعتبر الجزائر من بين الدول  التي تبحث عن فك ارتباط اقتصادها بقطاع المحروقات من خلال توفير المناخ استثماري  الملائم  و ازالة القيود امام حركة رؤوس الاموال الاجنبية. وتهدف هذه الدراسة القياسية الى تحليل طبيعة وحجم الاستثمارات الأجنبية المباشرة الوافدة الى الجزائر خلال الفترة الممتدة بين 1990 و 2014  مع التركيز على اهم العوامل المؤسساتية وتحديد اهم مكونات مخاطر البلد  المؤثرة  على استقطاب الاستثمارات الاجنبية المباشرة في الجزائر. وذلك بناء على المعطيات المقدمة من طرف مجموعة PRS group ومن خلال معطيات دليل مخاطر البلاد العالمي(ICRG). و من اجل التوصل الى النتائج تم الاعتماد على المنهج الوصفي التحليلي لوصف متغيرات الدراسة واسلوب الانحدار الخطى المتعدد .و بعد تطبيق مجموعة من الاختبارات الاحصائية تم التوصل الى ضرورة تخفيض المخاطر الاقتصادية مع الاشارة الى عدم الاعتماد المفرط على مداخيل المحروقات والتي  تمثل خطر حقيقي على الاقتصاد الوطني. الكلمات المفتاحية  : جاذبية الاستثمارات، مخاطر البلد التنويع الاقتصادي. Abstract:         Most of developed and developing countries in the world eagerly compete to attract foreign direct investment for its role in solving development problems. Algeria is among these countries is looking for unpacking the relationship between economy and the hydrocarbons sector By providing appropriate investment climate and remove barriers to the movement of foreign capital.         This standard study aims to analyze the nature and volume of FDI inflows to Algeria during the period between 1990 and 2014 with a focus on the most important institutional factors and to identify the most important risks affecting the country to attract foreign direct investment to Algeria. Using data provided by the PRS group and based on global risk guide (ICRG) .In this article, we rely on descriptive and analytical approach to describe the different variables of the study and with the application of a multi linear regression model and a set of statistical tests, the findings indicate that Algeria have to reduce its economic risk reduction with and the over-reliance on of hydrocarbons revenues which represent a real danger to the national economy. Keywords : Attractiveness of FDI ,country risk, diversification